Allocation initiale et marché des permis négociables d’émission de gaz à effet de serre : quelle équité pour favoriser l’acceptabilité ? - Elodie Brahic (Éditions en environnement VertigO, 2010)
International negotiations on climate change were organized around the allocation of tradable greenhouse gas emission permits. This work is related to a hypothetic 2030 situation, assuming that all countries will be on that date in such a system of regulation. It simulates the quantitative issues that could be related to different criteria for initial allocation of permits distinguishing systems called « pure », based on a single criterion among a panel (population, GDP, according to responsibility, grandfathering, cost reduction) and « hybrids » systems combining several criteria under explicit rules. These simulations highlight the quantitative importance of issues related to these choices in terms of justice and try to discuss the consequences that can be expected for countries that remain free to accept or not these criteria in the negotiations.